A new species and a new host record of Pseudoberkleasmium (Pseudoberkleasmiaceae, Dothideomycetes) from Cocos nucifera and Zea mays in northern Thailand - Tian, Xingguo; Tibpromma, Saowaluck; Karunarathna, Samantha C.; Dai, Dongqin; Lu, Yongzhong; Mapook, Ausana; Jayawardena, Ruvishika S. (Phytotaxa, 2022)
Two Pseudoberkleasmium taxa were obtained from decaying leaves and culms of Cocos nucifera and Zea mays in northern Thailand. Pseudoberkleasmium collections were compared with closely related taxa based on morphological characteristics and combined ITS, LSU, SSU, TEF1-α, and RPB2 DNA sequence data. Pseudoberkleasmium chiangraiense sp. nov. and a new host record, P. chiangmaiense are presented with full descriptions, photo plates, and a phylogenetic tree showing the placements of taxa.